Validity and Reliability of a Phone App and Stopwatch for the Measurement of 505 Change of Direction Performance: A Test-Retest Study Design - Chen, Zhili; Bian, Chao; Liao, Kaifang; Bishop, Chris; Li, Yongming (Frontiers in Physiology, 2021)
Purpose: The aim of this study was to explore the validity and reliability of a phone app (named: COD timer) and stopwatches for the measurement of change of direction (COD) performance. Methods: Sixty-two youth basketball players (age: 15.9 ± 1.4 yrs, height: 178.8 ± 11.0 cm, body mass: 70.0 ± 14.1 kg) performed six trials of 505 COD test (with the left side being the plant leg first, then the right side). The completion time was measured simultaneously via timing gates (with error correction processing algorithms), the phone app and stopwatches. Results: There was an almost perfect correlation and agreement between timing gates and COD timer (r = 0.978; SEE = 0.035 s; LoA = -0.08 0.06 s), but a lower correlation and agreement between timing gates and stopwatch (r = 0.954; SEE = 0.050 s; LoA = -0.17 0.04 s) with statistical significance in completion time (ES = 1.29, 95%CI: 1.15-1.43, p < 0.01). The coefficient of variation revealed similar level of dispersion between the three timing devices (timing gates: 6.58%; COD timer: 6.32%; stopwatch: 6.71%). Inter-observer reliability (ICC = 0.991) and test-retest reliability (ICC = 0.998) were excellent in COD timer, while the inter-observer reliability was lower (ICC = 0.890) in the stopwatches. Conclusion: In the 505 COD test, the COD timer was able to provide a valid and reliable measurement. On the contrary, stopwatch was not recommended because of large error. Thus, if timing gates are unavailable, practitioners can adopt the COD timer app to assess 505 COD speed times.